2015
DOI: 10.1111/1467-954x.12238
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Gender and Work Segregation in the Cultural Industries

Abstract: This chapter addresses work ‘segregation’ by sex in the cultural industries. We outline some of the main forms this takes, according to our observations: the high presence of women in marketing and public relations roles; the high numbers of women in production co-ordination and similar roles; the domination of men of more prestigious creative roles; and the domination by men of technical jobs. We then turn to explanation: what gender dynamics drive such patterns of work segregation according to sex? Drawing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 21 publications
2
93
0
11
Order By: Relevance
“…This work highlights the ways that informality, precariousness, reliance on reputation and the centrality of networks disadvantage women (Banks, Gill, & Taylor, 2013;Conor, Gill, & Taylor, 2015;Finkel, Jones, Sang, & Russell, 2017;Handy & Rowlands, 2014;Wreyford, 2015). Other scholars have shown that gender stereotypes are used to justify occupational sex segregation within creative industries, wherein men hold positions with more power (Hesmondhalgh & Baker, 2015), and that low-end (or 'below-the-line') creative professions are structured around sexism, classism and stereotypically gendered job roles (Jones & Pringle, 2015). Other scholars have shown that gender stereotypes are used to justify occupational sex segregation within creative industries, wherein men hold positions with more power (Hesmondhalgh & Baker, 2015), and that low-end (or 'below-the-line') creative professions are structured around sexism, classism and stereotypically gendered job roles (Jones & Pringle, 2015).…”
Section: Literature Reviewmentioning
confidence: 90%
“…This work highlights the ways that informality, precariousness, reliance on reputation and the centrality of networks disadvantage women (Banks, Gill, & Taylor, 2013;Conor, Gill, & Taylor, 2015;Finkel, Jones, Sang, & Russell, 2017;Handy & Rowlands, 2014;Wreyford, 2015). Other scholars have shown that gender stereotypes are used to justify occupational sex segregation within creative industries, wherein men hold positions with more power (Hesmondhalgh & Baker, 2015), and that low-end (or 'below-the-line') creative professions are structured around sexism, classism and stereotypically gendered job roles (Jones & Pringle, 2015). Other scholars have shown that gender stereotypes are used to justify occupational sex segregation within creative industries, wherein men hold positions with more power (Hesmondhalgh & Baker, 2015), and that low-end (or 'below-the-line') creative professions are structured around sexism, classism and stereotypically gendered job roles (Jones & Pringle, 2015).…”
Section: Literature Reviewmentioning
confidence: 90%
“…McCann (2005) suggests that sexual harassment in the workplace is also underreported. Sexism is flexible and dynamic (Gill, 2011(Gill, , 2014, and Hesmondhalgh and Baker (2015) posit that sexual harassment in the creative industries is often malleable, agile and subtle. Littler-Bishop et al (1982) emphasize that women might not report harassment because they fear it will be detrimental to their career advancement.…”
Section: The Creative Industries and Sexual Harassmentmentioning
confidence: 99%
“…A second area of knowledge on barriers to women's participation and advancement centred on gendered perceptions. This gender knowledge, firstly, described typical perceptions of women and how, regardless of their truth value (Hesmondhalgh & Baker, ), these perceptions impacted employment prospects. Studies evidenced perceptions of women as more suited to caring, nurturing, communicating and operational management, and to working on less serious topics such as children's programmes and quiz shows (Hesmondhalgh & Baker, ; Mills & Ralph, ; World Association for Christian Communication, ).…”
Section: The Gender Knowledge For the Uk Screen Sector: An Ecology Pementioning
confidence: 99%
“…This gender knowledge, firstly, described typical perceptions of women and how, regardless of their truth value (Hesmondhalgh & Baker, 2015), these perceptions impacted employment prospects. Studies evidenced perceptions of women as more suited to caring, nurturing, communicating and operational management, and to working on less serious topics such as children's programmes and quiz shows (Hesmondhalgh & Baker, 2015;Mills & Ralph, 2015; World Association for Christian Communication, 2015). Women were also seen as "risky" in a way men are not (European Women's Audiovisual Network, 2016a, p. 191) and, in the case of mothers, as not having enough 'hunger'…”
Section: Representationsmentioning
confidence: 99%